Hydrological Modelling of River Basin and Strategic Management of Watershed under Different Anthropogenic and Climate Change Scenarios: A Case Study of Genale Catchment, Ethiopia - Negewo, Tufa Feyissa (My University, 2022)
It is important to estimate the quantity and quality of water resources in terms of spatial and temporal variability to utilize it sustainably. Change in future climate conditions affects the availability of water resources by modifying the magnitude of precipitation, groundwater recharge, surface runoff, actual evapotranspiration, lateral flow, water yield, the river flows, and provoke water stress in the downstream. Local government authority around the globe is also emphasizing water resources project exploration, design, planning, and management aspect within the river basin.
Sarma, Arup Kumar
Keywords: Hydrological Model; Water Yield; Soil Erosion/Sediment Yield; Climate Change; LULC Change; Ecological Management Practices (EMPs)